(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
The emerging public awareness of health care and nutrition endorses the capability of phytochemicals like dietary fibre and polyphenols on their health-desirable characteristics. Thus, it is necessary to recognize contemporary sources of nutraceuticals and other wholesome, natural products that have the desired practical qualities. Finger millet, one of the lesser-known crops has renowned recognition with its health advantages, with certain benefits attributed to its polyphenols and dietary fibres. Its protein and lipid content are equivalent to that of rice, and it surpasses rice and wheat in terms of mineral and micronutrient levels. In terms of nutrition, it has an exceptional amount of calcium (344 mg/100g) and dietary fibre (15–20%) and phenolic compounds (0.3% to 0.3%). The crop’s resistance to environmental stresses including drought and deficient soil fertility further emphasises how important it is for guaranteeing food security in harsh climes. The inadequate availability of proper marketing channels for these crops has accelerated their decline both in production and consumption level. The creation of value-added products, together with focused breeding efforts for production enhancement and improved nutritional value, are methods to maximize the potential of finger millet. This review aims to investigate various applications of finger millet, its utilization, bio accessibility, and possible health advantages, in an effort to encourage further research.